Evaluación de sistemas agroforestales de café en ecosistemas de la provincia de Loja a través de los Índices de calidad del suelo (ICS) basados en servicios ecosistémicos - Guazha Romero, Brenda del Cisne (2025)
Soil quality in coffee agroforestry systems (AFS) in Quilanga, Espíndola and Gonzanamá, Loja province, is affected by senescent plantations, inefficient management, soil variability and marginal soils, which reduces productivity and the capacity to provide ecosystem services (ES). The lack of a standardized index makes monitoring and management difficult. It is crucial to improve soil quality and optimize coffee production; therefore, a soil quality index (SQI) was developed based on ecosystem services, integrating physical and chemical properties that allow its evaluation, facilitating decision making for sustainable management. A bibliometric study was used to identify indicators that relate to soil functions and ES in coffee FFS. Twenty indicators were considered as a total data set (CTD) between physical- chemical as a result of the bibliometric analysis. In addition, a sedimentation plot and a principal component analysis were performed to select those indicators with the highest correlation and form a minimum data set (MDC) from the CTD, composed of 15 indicators for Gonzanamá, 11 for Quilanga and 8 for Espíndola. Finally, they were normalized and integrated into an ICS through mathematical equations. The results show that the indicators that contributed the most weight to the ICS were: MO, CO, N for Espindola and Quilanga canton, while for Gonzanamá it was B, MO, CO and CE. The ICS for Gonzanamá showed moderate quality (0.40), Espíndola (0.22) and Quilanga (0.18) showed low and very low quality, respectively. The average soil quality in these areas is low. Key indicators, such as OM, CO and N, should be prioritized to improve coffee production and preserve essential ecosystem services.